Effective procedures for executive's preparation - Martínez Mondéjar, Elisabet; Vallejo Curbelo, Iraida; Milian Morales, Maritza (Avances en Supervisión Educativa, 2014)
The preparation of the University of Pedagogical Sciences executives is essential to ensure the development of the teachers that are preparing themselves to by promoting post focus on evaluation and promotion. This complex process demands concrete results to ensure new executives without affecting the organization results.The experience of the authors and the observation methods applied showed that there are still limitations in the process regarding the preparation for the development of the executives work with teachers that are preparing themselves to by promoting post. This article presents an efficient way solve  this problem gradually.The aim of this article is to present methodological procedure that facilitates the executives  work with teachers that are preparing themselves to by promoting post from their  workplace from  a manual directed towards counseling executives  on how to develop the focalization, the selection and the evaluation and promotion of its teachers that are preparing themselves to by promoting post  from the work system itself  of the different levels of management from the University of Pedagogical Sciences " Felix Varela Morales " of Villa Clara.
Keywords: procedures; preparation; executives